2019
DOI: 10.1038/s41699-019-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport in layer-by-layer assembled polycrystalline graphene films

Abstract: New technologies are emerging which allow us to manipulate and assemble 2-dimensional (2D) building blocks, such as graphene, into synthetic van der Waals (vdW) solids. Assembly of such vdW solids has enabled novel electronic devices and could lead to control over anisotropic thermal properties through tuning of inter-layer coupling and phonon scattering. Here we report the systematic control of heat flow in graphene-based vdW solids assembled in a layer-by-layer (LBL) fashion. In-plane thermal measurements (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…The sp 2 bonding between the carbon atoms in graphene creates three s-bonds, which are responsible for its high mechanical strength and high in-plane thermal conductivity. [38][39][40][41][42] Graphene's remarkable conductivity is associated with overlapping p z orbitals above and below the molecular plane, which creates a delocalized pelectron system to allow for free movement of electrons. These unique bonding characteristics give rise to a linear band structure with a zero-band gap near the K and K 0 points, leading to graphene's high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sp 2 bonding between the carbon atoms in graphene creates three s-bonds, which are responsible for its high mechanical strength and high in-plane thermal conductivity. [38][39][40][41][42] Graphene's remarkable conductivity is associated with overlapping p z orbitals above and below the molecular plane, which creates a delocalized pelectron system to allow for free movement of electrons. These unique bonding characteristics give rise to a linear band structure with a zero-band gap near the K and K 0 points, leading to graphene's high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…While these are widely used techniques, they are known to introduce defects to the graphene structure that are detrimental to electrical and thermal transport properties, while conversely improving chemical and electrochemical sensitivity. 1,5,42,[44][45][46][47][48] The method of fabricating electrochemical graphene sensors is vital in creating edge and basal plane defects to improve chemical sensitivity. Work such as Banerjee et al reported ultrahigh electrochemical current densities for graphene edges embedded in dielectric nanopores.…”
Section: Introductionmentioning
confidence: 99%
“…The heat transport in all bulk carbon allotropes is mostly carried by acoustic phonons, which are attributed to the strong covalent sp 2 bonding, leading to efficient heat transfer with lattice vibrations. [44][45][46][47][48] Moreover, the impurities and defects are the powerful primary factors that affect the phonon scatterings in graphene. 49 We consider that the small thermal conductivity in GOP before and aer lower uence irradiation is attributed to defects and lesser amounts of sp 2 carbons, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The thermal transport in carbon materials is mainly determined by acoustic phonons, and the phonon can be further inuenced by the defects and structure disorder. [44][45][46][47][48][49] The defects, disorder structure and the oxygen functional group are inuenced by proton irradiation, leading to the change in the thermal properties of GOP.…”
Section: Thermal Conductivitiesmentioning
confidence: 99%
“…4,5 Recently, graphene-based nanocomposites have attracted great interest in exploring efficient microwave absorption materials due to their exceptional chemical and physical properties such as low density, good chemical inertness, and excellent mechanical properties. [6][7][8][9] However, two major issues still need to be solved for their practical application, including the limitation of large-scale fabrication and poor impedance matching that resulted from the high dielectric constant and nonmagnetic property of graphene. As for the mass production of graphene, various strategies have been explored, such as mechanical exfoliation techniques, 10 chemical vapor deposition, 11 solid-state carbon source deposition, 12 solution exfoliation, 13 nanotube splitting and unzipping, 14,15 and chemical reduction of graphene oxide (GO).…”
Section: Introductionmentioning
confidence: 99%